Algorithm 762 LLDRLF, log-likelihood and some derivatives for log-F models. - Brown, Barry W.; Levy, Lawrence B.; Lovato, James; Russel, Kathy l.; Spears, Floyd M.
The flexible statistical models incorporating the log-F distribution are little used because of numeric difficulties. We describe a method for calculating the log-likelihood and two derivatives with respect to the data argument. Fortran subroutines incorporating these calculations are provided.
Keywords: Accelerated failure; Log-F distribution; Log-likelihood.